Acidogenic Evaluation of Pediatric Medications in Saudi Arabia - Gowdar, Inderjit M (J Pharm Bioallied Sci, 2020)
BACKGROUND: To gain patient compliance, pediatric medication preparations are made palatable by adding sugars such as sucrose, glucose, or fructose. These readily fermentable carbohydrates can significantly increase dental caries potential in the young and chronically sick children. OBJECTIVES: To evaluate acidogenic potential of commonly used pediatric liquid medicaments (PLMs). MATERIALS AND METHODS: The acidogenic potential is assessed by estimating the endogenous pH of PLM. RESULTS: The mean endogenous pH was higher in Azomycin (9.16 ± 0.25) and lowest in Lorinase (3.16 ± 0.15). CONCLUSION: Of nine, eight PLMs were acidic in nature.